Knowledge Regarding Healthful School Environment Among Teachers in Schools - Acharya, Shusma; Bashyal, Dakshina (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Background: Healthful school environment is one of the components of school health program which is essential for promotion and maintenance of healthy and safe learning as well as living environment. The objective of the study was to assess the knowledge regarding healthful school environment among teachers in school of Palpa. Method: A descriptive cross sectional design was carried out among 96 teachers working in Shree Damkada Model Secondary School, Saraswati Higher Secondary School and Shree Sarda Higher Secondary School. Probability proportionate sampling method was used and data was collected through self-administered questionnaire and analyzed by descriptive and inferential statistics using SPSS version 25 findings were presented in tabulated form. Findings: More than half (53.9%) had adequate level of knowledge. Adequate knowledge was present on meaning (59.8%), purpose (89.6%), important of boundary for school (100.0%), classroom structure with minimized distraction and hazard to students (69.8%), comfort and ergometric design of classroom furniture (62.5%), color of board used in classroom(71.9), necessary of cross ventilation (86.5%), necessary of separate eating facility (100.0%), necessary of separate toilet facility (100.0%), safe method for waste disposal (71.9%). However inadequate knowledge was present regarding appropriate location for school (32.3%), area needed for a student (34.4%), ideal number of students in one classroom (2.0%), size of playground for school (10.4%). There was no significant association found level of knowledge and socio-demographic variables. Conclusion: More than half of the respondents have adequate level of knowledge regarding healthful school environment despite of this there is inadequate level of knowledge regarding appropriate location for school, area needed for one student, ideal number of students in one classroom. This indicates need of in-service education program on healthful school environment.